1999
DOI: 10.1046/j.1469-1809.1999.6330249.x
|View full text |Cite
|
Sign up to set email alerts
|

A statistically robust variance‐components approach for quantitative trait linkage analysis

Abstract: summaryPreviously we showed ) that a statistically robust version of the Haseman & Elston (1972) sib-pair method greatly increased power to detect linkage in the presence of outliers. In this paper we report on M-estimation to accommodate outliers in the variancecomponents approach to linkage analysis developed by Amos (1994). Simulations show that in the presence of outliers the robust variance-components approach provides substantially greater power, more precise estimation of heritabilities, and better fals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…(60) This could be the likeliest reason underlying detection and replication of quantitative trait loci (QTL) in severely under powered studies by the same study group (also see Are replicated findings always true?). In addition, robust approaches that can accommodate outliers (68)(69)(70) are valuable alternatives.…”
Section: Quality Controlmentioning
confidence: 99%
“…(60) This could be the likeliest reason underlying detection and replication of quantitative trait loci (QTL) in severely under powered studies by the same study group (also see Are replicated findings always true?). In addition, robust approaches that can accommodate outliers (68)(69)(70) are valuable alternatives.…”
Section: Quality Controlmentioning
confidence: 99%
“…Issues on robustness have been popularly addressed in statistical inference when there exist nuisance parameters that interfere with the powers of the studied tests. In genetic studies, this issue has also been investigated widely by researchers (Wang et al, 1999; Gastwirth & Freidlin, 2000; Kraft, 2001; Zheng et al, 2002; Xu et al, 2003; Diao & Lin, 2005; Tai & Hou, 2006; Yan et al, 2008; Wang et al, 2008). To obtain robust statistics over all plausible genetic models, we have referred to the studies of Davies (1977) and Zheng & Chen (2005).…”
Section: Discussionmentioning
confidence: 99%
“…Inferences using the likelihood ratio test and inappropriately assuming multivariate normality can be inaccurate when the underlying trait data display either skewness or kurtosis. Wang et al 70 proposed a data trimming approach in which extreme observations are replaced by a specified quantile. For instance, if the data are trimmed to the 99th percentile, then any observations more extreme than the 99th percentile are replaced by the 99th quantile of the data.…”
Section: Variance-components Approachesmentioning
confidence: 99%
“…We also detected some excess of false positive findings when there was a large genetic background, consistent with findings from Allison et al 68 who found that marked non-normality affects the nominal type I error rate of likelihood ratio tests for the VC method . These results indicate the need to implement robust, 70 semiparametric 51,71 or Monte-Carlo 72 tests when studying ascertained data, when the total heritability of the trait is high. When multivariate phenotypes are considered or when multiplex sampling is used, equation ( 4) is modified to be based upon the multivariate normal distribution.…”
Section: Selectionmentioning
confidence: 99%